Wednesday

August 20, 2014

August 20, 2014

Posted by **jason** on Sunday, July 8, 2007 at 10:30pm.

I need a hint on how to solve this

Look for the first root by graphical means or trial-and-error. Note that when x=2,

x^3-5x^2-4x+20 = 8-20 -8 +20 = 0.

Therefore 2 is one root and x-2 is a factor.

Next, divide x-2 into x^3-5x^2-4x+20 using long division, to get a quadratic factor. The result is

(x-2)(x^2-3x-10)

The quadratic factor is just (x-5)(x+2), so the equation becomes

(x-2)(x+2)(x-5) = 0

This tells you that the other roots are x = -2 and +5.

**Related Questions**

algebra - solve 4^3x-4=32^x+2 Please help! Do you mean 4^(3x) -4 = 32^x +2 ? yes...

logarithmic eq: - 3logx = 6-2x Thanks This is a problem that is best solved by ...

algebra - solve for x (24+2x)(10+2x) - 240 = 152 First multiply. 24(10) = ___ 2x...

Math - I can't for the life of me solve this! 6x^2-23x+15=0 6x^2-23x+15 = (a x...

help! - A horizontal translation is applied to the graph of y= X^ 3 + 2 so that ...

need help in math, - Translate to a system of equations and solve using the ...

Pre Algebra - Please help me with some problems. Thank you! Solve the equation ...

algebra - Im lost i dont know how to do this can someone show me step by step ...

algebra - Im lost i dont know how to do this can someone show me step by step ...

math - Still looking at how to solve these... Both are cubic polynomials? 43x^3...